Phytotoxic Effect of Aqueous Extract of Lantana Camara L. Leaves on Germination and Early Growth of Rice (Oryza sativa L. cv. Cempo Merah) - Khasanah, Rita Ariyana Nur (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The use of aqueous extracts from certain plants in controlling weeds is gaining attention in eco-friendly agriculture due to their allelopathic activity. One of the plants that has been investigated as a potential bioherbicide for controlling various weeds is Lantana camara L. Its extract has been tested on several non-targeted plants and has been shown to inhibit their germination. This study aimed to examine the effect of bioherbicide (aqueous extract of Lantana camara L. leaves) on rice (Oryza sativa L. cv. Cempo Merah) as a non-targeted plant. Methods: This experimental study used a completely randomized design with three replications. Concentration series of the aqueous extracts from L. camara L. leaves (0%, 25%, 50%, 75%, and 100%) were tested on rice seeds that were germinated on petri dishes for 14 days. Results: The results showed that the aqueous extract of L. camara L. leaves had a phytotoxic effect on germination and early growth of rice (Oryza sativa L. cv. Cempo Merah). Conclusions: The highest concentration exhibited the greatest phytotoxicity. Allelopathy chemicals in L. camara L. leaves were responsible for these effects.